2020
DOI: 10.1038/s41541-020-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid moieties of Mycoplasma pneumoniae lipoproteins are the causative factor of vaccine-enhanced disease

Abstract: Vaccine-enhanced disease (VED) occurs as a result of vaccination followed by infection with virulent Mycoplasma pneumoniae. To date VED has prevented development of an efficacious vaccine against this significant human respiratory pathogen. Herein we report that vaccination of BALB/c mice with M. pneumoniae lipid-associated membrane proteins (LAMPs) induces lung lesions consistent with exacerbated disease following challenge, without reducing bacterial loads. Removal of lipid moieties from LAMPs prior to vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Researchers in the 1960’s attempted to develop vaccines for M. pneumoniae using formalin-inactivated whole pathogen, but these efforts were stymied by the observation that some vaccinated individuals experienced enhanced clinical symptoms upon subsequent infection in comparison to unvaccinated control subjects 23 . This finding, later termed Vaccine-Enhanced Disease (VED), has been recapitulated in mouse models of M. pneumoniae infection, and has stood as a roadblock to successful vaccine development for several decades 24 27 . Prior exposure to live or inactivated M. pneumoniae followed by subsequent challenge consistently leads to increased lung pathology characterized by enhanced leukocyte infiltration and perivascular/peribronchiolar cuffing 24 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in the 1960’s attempted to develop vaccines for M. pneumoniae using formalin-inactivated whole pathogen, but these efforts were stymied by the observation that some vaccinated individuals experienced enhanced clinical symptoms upon subsequent infection in comparison to unvaccinated control subjects 23 . This finding, later termed Vaccine-Enhanced Disease (VED), has been recapitulated in mouse models of M. pneumoniae infection, and has stood as a roadblock to successful vaccine development for several decades 24 27 . Prior exposure to live or inactivated M. pneumoniae followed by subsequent challenge consistently leads to increased lung pathology characterized by enhanced leukocyte infiltration and perivascular/peribronchiolar cuffing 24 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Huang and colleagues have indicated that the lipidassociated membrane proteins of U. parvum and U. urealyticum induce U937 cell cycle arrest in the G1 phase through a p21-dependent but p53-independent pathway [274], suggesting that this signaling pathway is highly correlated with the inflammatory and protective effects in ureaplasmal diseases. Interestingly, a recent report has indicated that the lipid moiety of M. pneumoniae lipoprotein is a causative factor of vaccine-enhanced disease, which overcomes the roadblock of vaccine development [14]. This suggests that the development of a vaccine should balance the maintenance of its immune-stimulatory activity and reduce the side effects caused by the lipid moiety.…”
Section: Membrane Lipoproteinsmentioning
confidence: 99%
“…Mycoplasmas can also express various pathogenic enzymes such as lipolytic enzymes, peptidases, phosphatases, ecto-ATPases, cytotoxic nucleases and nucleotidases, that are considered important mycoplasma pathogenic factors [12,13]. Furthermore, some inherent components located at the mycoplasma cell membrane, such as lipids, membrane lipoproteins, and even superantigens produced by Mycoplasma arthritidis, could trigger an inflammatory response through various strategies (Figure 1) [14][15][16]. Although several questions remain unanswered, significant progress has been made in identifying the virulence factors by which mycoplasmas interact with and subsequently damage the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two biological replicates of Lag3 À/À and three of WT cells were assessed in triplicate per condition. All samples were prepared for proteomic analysis using filter-aided sample preparation, as previously described, with a few modifications (16,17). Briefly, a 200-mg protein whole cell lysate aliquot was removed and diluted with UA buffer (8 M urea in 0.1 M Tris HCl [pH 8.5]), and protein Cys residues were reduced using 25 mM DTT in UA for 1.5 h at 37 C. Directly afterward, the sample solutions were loaded onto a Microcon YM-10 10 kDa molecular mass cutoff filter (Thermo Fisher Scientific) previously conditioned with intact BSA (Sigma-Aldrich) and washed thoroughly.…”
Section: Adoptive Ot-ii Cell Transfer Experimentsmentioning
confidence: 99%